2013
DOI: 10.1016/j.nuclphysb.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Notes on holographic superconductor models with the nonlinear electrodynamics

Abstract: We investigate systematically the effect of the nonlinear correction to the usual Maxwell electrodynamics on the holographic dual models in the backgrounds of AdS black hole and AdS soliton.Considering three types of typical nonlinear electrodynamics, we observe that in the black hole background the higher nonlinear electrodynamics correction makes the condensation harder to form and changes the expected relation in the gap frequency, which is similar to that caused by the curvature correction. However, in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 67 publications
(87 reference statements)
8
62
0
Order By: Relevance
“…In [65], the author discussed a simple example of a Born-Infeld-like Lagrangian with a logarithmic term which can be added as a correction to the original Born-Infeld one. Replacing the Maxwell field with the nonlinear electromagnetic field, it was disclosed from the behavior of the boundary operator in the CFT that the nonlinearity in Born-Infeld and the logarithmic form fields can make holographic superconductor difficult to form [19,66]. In the corresponding bulk spacetime, it was observed that the nonlinearity of the electromagnetic field can hinder the growing mode to appear in the scalar perturbation [67], which is consistent with the phenomenon on the boundary CFT.…”
Section: Jhep02(2016)116supporting
confidence: 56%
“…In [65], the author discussed a simple example of a Born-Infeld-like Lagrangian with a logarithmic term which can be added as a correction to the original Born-Infeld one. Replacing the Maxwell field with the nonlinear electromagnetic field, it was disclosed from the behavior of the boundary operator in the CFT that the nonlinearity in Born-Infeld and the logarithmic form fields can make holographic superconductor difficult to form [19,66]. In the corresponding bulk spacetime, it was observed that the nonlinearity of the electromagnetic field can hinder the growing mode to appear in the scalar perturbation [67], which is consistent with the phenomenon on the boundary CFT.…”
Section: Jhep02(2016)116supporting
confidence: 56%
“…Second, if E || B 0 (parallel polarization), from (19) E 2 = 0, and from (20) we get k 2 w 2 = ε 33 μ 22 . In this case, the corresponding dispersion relation becomes…”
Section: Born-infeld-like Modelmentioning
confidence: 96%
“…Additionally, nonlinear electroa e-mail: patricio.gaete@usm.cl b e-mail: helayel@cbpf.br dynamics (BI) has also been investigated in the context of gravitational physics [17,18]. Actually, in addition to BornInfeld theory, other types of nonlinear electrodynamics have been studied in the context of black hole physics [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…cal temperature of a holographic superconductor [48]. Furthermore, in recent studies on holographic superconductors, it has been shown that the exponential nonlinear electrodynamics can increase the critical values of the external magnetic field as the temperature goes to zero [49].…”
Section: Jhep03(2016)037mentioning
confidence: 99%
“…[46] and [51], respectively. Besides, it was argued that in applications of the AdS/CFT correspondence to superconductivity, exponential nonlinear electrodynamics, makes crucial effects on the condensation as well as the critical temperature of the superconductor [48]. It was also recently observed that, in the holographic superconductor, the exponential nonlinear electrodynamics can increase the critical values of the external magnetic field as the temperature goes to zero [49].…”
Section: Jhep03(2016)037 4 Summary and Concluding Remarksmentioning
confidence: 99%